PHENETIC ANALYSIS OF THE IRANIAN SPECIES OF THE BROMUS SECTIONS GENEA, NEOBROMUS AND NEVSKIELLA (Journal of Sciences, Islamic Republic of Iran)
A phenetic analysis of the 12 taxa or operational taxonomic units (OTUs) belonging to the three sections; Genea, Neobromus, and Nevskiella of the genus Bromus was performed. Unweighted pair-group method using arithmetic averages (UPGMA) and weighted pair-group method using arithmetic averages (WPGMA) clustering and factoriel method analyses were used to set the taxa apart. Forty-four characters including 4 vegetative and 38 reproductive characters, the chromosome number and the geographical distribution were considered in this study. The outcomes of multivariate analyses were compared with different conventional classifications. The results show that four major phenetically well-defined groups existed which confirmed the Sale's concept. This finding, however, is in odd with that expressed in Flora of U.S.S.R. The relations between the taxa were discussed, and a key to identify them was presented.